Newly diagnosed systemic lupus erythematosus in a COVID-19 positive patient: a case report - Abdul Rahman, Nurul Aimi; Tuan Soh, Tuan Suhaila; Mahayidin, Hasni (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Systemic lupus erythematosus (SLE) is an autoimmune disease with a wide range of clinical presentations. Its early manifestations may not be specific thus proper investigations and diagnosis may be hindered. Coronavirus disease (COVID-19), primarily an infectious respiratory illness, is caused by the novel coronavirus SARS-CoV-2 that was recently discovered in 2019. We report a case of a newly diagnosed SLE in a COVID-19 patient who presented with worsening fluid retention and renal function.